Effects of NGNs on market definition - Pereira, João Paulo (2014)
Historically, electronic communications networks were built to support specific services. For example, fixed and mobile telephone networks were developed to support voice telephone calls, whereas cable networks, satellites, and over-the-air broadcasts were built to support television services (unidirectional linear video). However, these communications networks are currently incorporating new technology and are rapidly evolving into multi-service networks that support voice, video, and data over a single, fully integrated communications platform. NGNs provide to customer access to a large range of services, leading to the increase of the bandwidth demand - For example, if customers encounter their demand on a single network, a triple play product, the bandwidth demand for that network will increase. Moreover, the migration to NGN may require upgrades to the infrastructure to provide sufficient service quality. The entry of new competitors can be based on the resale of services from the incumbent, on building up their own infrastructures, on renting unbundled infrastructure from incumbents, or, on the combination of the above elements. The availability of these options to competitors and price definition are generally determined by regulatory policies. So, the introduction of NGNs by telecommunication network operators obligates the national regulators adapt their access regulation regimes to the new technological conditions. Regulation and/or promotion of competition by regulatory measures need to be analyzed and compared. So, in this paper we explore the role of competition policy and regulation.